Internal Conflicts in Works of Thucydides and Machiavelli - Jakub Šedo (Vojenské rozhledy, 2020)
Hybrid threats are considered among the most serious risks that Western societies currently face. The aim of actors using such threats is to influence decision-making processes, and in order to do so they use a rich spectrum of methods to instigate conflict in society, seeking to undermine trust in institutions, abet radicalisation, and so on. Activities aimed at creating internal conflict, and the prevention of such activities, are not, of course, a new phenomenon; they differ only in their extent, intensity and the techniques used. The aim of this paper is to investigate how classic strategists – Thucydides and Machiavelli – described in their works how internal conflict is fomented among the enemy and how it can be prevented. The paper describes and analyses various ways of instigating and mitigating internal conflict as noted in their works, and assesses their relevance for the current debate.